An analysis of the effects of different urban park space environment construction on national health - Zhang, Weijian; Yang, Boyi; Wang, Ruijing; Guo, Xitie (Frontiers in Environmental Science, 2024)
Urban green spaces, including parks, plazas, and squares, are essential components of healthy and sustainable cities. These areas play a central role in enhancing the wellbeing of citizens, fostering social interactions, and promoting sustainable urban development. This study investigates the multifaceted benefits of integrating green spaces into urban environments, such as improving physical and mental health, facilitating social engagement, and supporting environmental sustainability. Despite these benefits, the development and maintenance of urban green spaces face significant challenges, including limited suitable land, financial constraints, and inadequate access, which can exclude certain populations from enjoying these green havens. The study examines specific case studies, including Linyi People’s Park, Lanshan Youth Park, and Yumin Park, to highlight the factors contributing to the success or failure of these spaces. It also draws inspiration from international examples like New York City’s High Line and Germany’s Emscher Landscape Park, which have successfully transformed neglected areas into vibrant green oases. The findings underscore the importance of adopting principles of spatial justice, resource management, urban policy revision, and access reform to ensure the equitable distribution and accessibility of urban green spaces. The study concludes with key recommendations for urban planning and public health policy, aiming to enhance the wellbeing of citizens and strengthen the harmonious relationship between urban development and the natural environment. This study explores the multifaceted benefits of urban green spaces, including parks and plazas, highlighting their critical roles in enhancing physical and mental health, fostering social interactions, and promoting environmental sustainability. Through in-depth case studies of Linyi People’s Park, Lanshan Youth Park, and Yumin Park, the research identifies key factors contributing to the success and challenges of these spaces. Innovations in the study include a holistic analysis of green space benefits, a focus on spatial justice for equitable access, and comparative insights from international examples like New York City’s High Line and Germany’s Emscher Landscape Park. The research identifies several gaps, including the need for longitudinal studies on health impacts, understanding socioeconomic and cultural variability in green space use, evaluating the effectiveness of policy interventions, exploring technological integration, assessing environmental and economic trade-offs, and developing models for community engagement and ownership. Addressing these gaps will enhance strategies for integrating green spaces into urban environments, ensuring their benefits are accessible to all citizens.